Theonyms in Royal Titulature Among the Classic Maya: A Follow-Up - Beloborodov, Niketas (Onomástica desde América Latina, 2025)
This article complements a previously published study on the unusual Classic Maya onomastic pattern of certain theonyms appearing among the titles of noblemen. The approach that identifies this pattern as a “short formula” of deity impersonation allows for exploring more peculiar cases and distinguishing them from theophoric anthroponyms.